Uso de las técnicas grafoplásticas y su influencia en el desarrollo de la psicomotricidad en los niños de educación inicial de la Unidad Educativa Ciudad de Vinces - Rugel Briones, Stefania Marilú (2023)
Graphoplastic techniques include the participation of children through drawing, painting and actions such as cutting, tearing, crumpling, assembling, folding and cutting with scissors or fingers, among others, with the purpose of promoting the development of skills in the early stages. of infant development. That is why the present case study aims to determine the use of graph-plastic techniques and their influence on the development of psychomotor skills in early education children. A qualitative investigation was carried out by applying surveys to the Early Education teacher and parents; the descriptive and exploratory method was also used to collect information. The results showed the need to apply graphoplastic techniques to promote psychomotor skills in infants since they present difficulties in the development of activities in which fine and gross motor skills are used. As a result of the research process, it is concluded that applying graphoplastic techniques will contribute to the improvement of the infant's psychomotor skills, promoting adequate control of hand and finger movements, which will facilitate the effective performance of activities such as writing, drawing and manipulation of small objects.